2021
DOI: 10.1021/acs.jchemed.0c00092
|View full text |Cite
|
Sign up to set email alerts
|

Getting Students Back on Track: Persistent Effects of Flipping Accelerated Organic Chemistry on Student Achievement, Study Strategies, and Perceptions of Instruction

Abstract: Converting a first-term, accelerated summer organic chemistry course to a flipped format reduced the achievement gap in the flipped course and in the second-term traditional lecture course between Non-Repeaters taking an accelerated course to "get ahead" and Repeaters taking the course to "get back on track." The difference in final exam performance in the second-term course was nearly halved, the GPA gap in both courses was reduced, and the gap in passing rate for the second-term course was eliminated. While … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…Several studies have recognized that the flipped classroom approach effectively optimizes learning among higher education chemistry students [40][41][42][43]. Considering the importance of chemistry education in the national curriculum, society, and the relevance of the field to the chemical industry for a sustainable future generation, more research is therefore needed.…”
Section: Related Literaturementioning
confidence: 99%
“…Several studies have recognized that the flipped classroom approach effectively optimizes learning among higher education chemistry students [40][41][42][43]. Considering the importance of chemistry education in the national curriculum, society, and the relevance of the field to the chemical industry for a sustainable future generation, more research is therefore needed.…”
Section: Related Literaturementioning
confidence: 99%
“…On Mondays and Wednesdays, active learning was interspersed with lecturing, with collaborative learning dominating the activities. On “Flipped Fridays”, students worked in groups to solve problems, and I went over the Friday POW assignment answers. ,, Discussion section followed the same format as prepandemic discussions, and one discussion each week was recorded.…”
Section: Back In-person! What Happened To Engagement?mentioning
confidence: 99%
“…More recently, He et al. observed that a partially flipped undergraduate general chemistry course generally improved student performance in the subsequent course in the sequence, with a more pronounced effect for students with weaker incoming academic preparation, and Reimer et al reported that a flipped classroom implementation in an accelerated summer course for undergraduate organic chemistry reduced the performance gap between students who were repeating the course relative to students taking the course for the first time (implying the flipped classroom intervention provided even greater benefit to less academically prepared students) . This reduction in the achievement gap was observed in both the first-term course taught in a flipped format and in the subsequent course that was taught in a traditional format, and participating in the first-term flipped course appeared to significantly improve final exam performance for first-generation students .…”
Section: Introductionmentioning
confidence: 97%
“…observed that a partially flipped undergraduate general chemistry course generally improved student performance in the subsequent course in the sequence, with a more pronounced effect for students with weaker incoming academic preparation, and Reimer et al reported that a flipped classroom implementation in an accelerated summer course for undergraduate organic chemistry reduced the performance gap between students who were repeating the course relative to students taking the course for the first time (implying the flipped classroom intervention provided even greater benefit to less academically prepared students) . This reduction in the achievement gap was observed in both the first-term course taught in a flipped format and in the subsequent course that was taught in a traditional format, and participating in the first-term flipped course appeared to significantly improve final exam performance for first-generation students . Though a meta-analysis that accounts for publication bias has not yet been carried out to determine the broader impact on at-risk populations, the results summarized here suggest the flipped classroom has the potential to close the equity gap in gateway chemistry course outcomes and should alleviate concerns of instructors who worry about the ability of less prepared students to successfully navigate the independent preclass learning environment.…”
Section: Introductionmentioning
confidence: 99%